Evaluation of Post Cementation Marginal Seating of Monolithic Zirconia Crown Restorations Using Different Preparation Designs (A comparative in vitro study) - Adel F. Ibraheem1, Lena S. Abdullah2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The purpose of this in vitro study was to evaluate post-cementation vertical marginal seating of full contour zirconia crown restorations using different finish line designs (deep chamfer and shoulder) with different occlusal reduction schemes (planar and flat).Materials and Method: Thirty-two sound maxillary first premolar teeth freshly extracted for orthodontic purposes were collected to be used in this study. Teeth were divided into two main groups according to the design of finishing line used (n=16): Group A: Deep chamfer; Group B: Shoulder. Each group was then subdivided into two subgroups according to the scheme of occlusal reduction used (n=8): (A1, B1) Planar; (A2, B2) Flat. Standardized preparation for full contour zirconia crown restorations was carried out with finishing lines depth 1.0 mm, total convergence angle of 6 degrees and axial height 4 mm (buccally and palatally).Results: The results of this study showed that there were statistically highly significant differences among different groups (p < 0.01) using one-way ANOVA analysis and Student’s t-test. Additionally, comparison of significance between each pair of subgroups at pre and post-cementation intervals using Paired-Samples t-test showed a statistically highly significant differences.Conclusions: Deep chamfer with planar occlusal reduction scheme provided better marginal fit compared to that obtained with shoulder. On the other hand, shoulder with flat occlusal reduction scheme provided better marginal fit compared to that obtained with deep chamfer. Concerning the effect of the cementation procedure, the marginal gap was increased post-cementation as compared with the pre-cementation gap for all subgroups, but still within the clinically acceptable limit.